2008
DOI: 10.1242/dev.014282
|View full text |Cite
|
Sign up to set email alerts
|

FGF signals guide migration of mesenchymal cells, control skeletal morphogenesis and regulate gastrulation during sea urchin development

Abstract: The sea urchin embryo is emerging as an attractive model to study morphogenetic processes such as directed migration of mesenchyme cells and cell sheet invagination, but surprisingly, few of the genes regulating these processes have yet been characterized. We present evidence that FGFA, the first FGF family member characterized in the sea urchin, regulates directed migration of mesenchyme cells, morphogenesis of the skeleton and gastrulation during early development. We found that at blastula stages, FGFA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 77 publications
3
88
0
Order By: Relevance
“…Growth sp. (Röttinger et al, 2008). It is also known that PMCs remain as a disorganized cell 698 population without cellular extensions near the vegetal pole when inhibitors disrupt 699 FGFA signaling.…”
Section: Embryogenic Impairments During Chemical Stress 687mentioning
confidence: 99%
“…Growth sp. (Röttinger et al, 2008). It is also known that PMCs remain as a disorganized cell 698 population without cellular extensions near the vegetal pole when inhibitors disrupt 699 FGFA signaling.…”
Section: Embryogenic Impairments During Chemical Stress 687mentioning
confidence: 99%
“…Duloquin et al (2007) demonstrated that localized VEGF acts as both a guidance cue for the formation of ventrolateral PMC clusters and a signal for the differentiation of skeletogenic cells. On the other hand, Röttinger et al (2008) showed that FGF signaling plays an essential role in the guidance of PMC migration and the direction of skeletal morphogenesis. However, defects in skeletogenesis induced by Mpar6 injection were unlikely due to either the loss of skeletogenic cell differentiation or a lack of ectodermal guidance/direction cues required for skeletogenesis, since in Mpar6 embryos, mesenchyme cells expressed the PMC-specific P4 antigen ( Fig.…”
Section: Par6 Is Required For Skeletogenesis and Gut Differentiationmentioning
confidence: 99%
“…3j; Shimizu et al 1988) and VEGF/FGF-dependent skeletogenic genes, such as sm50 and sm30 (Fig. 3a,m;Duloquin et al 2007;Röttinger et al 2008), and because their descendants expressing the B2C2 antigen ( Fig. 3l; Leaf et al 1987) were allocated on the inner ectoderm wall in a pattern that prefigures the rod branching patterns, i.e., the anterolateral, transverse, postoral, and body rods (Fig.…”
Section: Par6 Is Required For Skeletogenesis and Gut Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinopluteus and ophiopluteus are similar not only in the presence of the larval skeleton, but also in the shape of the skeleton. The shape of the skeleton is achieved by interaction with the epidermis (Kinoshita and Okazaki 1984;Armstrong et al 1993;Di Bernardo et al 1999;Duloquin et al 2007;Röttinger et al 2008). Some common feature may exist in the larval epidermis of echinoderms that led to a similar interaction with the skeletogenic mesenchyme cells.…”
Section: Molecular Evolution Of the Heterochronic Shift Of Skeletogenmentioning
confidence: 99%